Jordan : Technical Assistance Report-Monetary and Financial Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance report on Jordan discusses that financial system of Jordan is dominated by other depository corporations (ODC), which constitute around 63 percent of the financial system's assets. The technical assistance mission delivered objectives and agreed with the authorities on an action plan to improve the country's monetary statistics. Some progress has been made in the Central Bank trial accounts regarding the sectorization and classification of the financial instruments. The Central Bank of Jordan (CBJ) has made substantive progress in improving human resource skills among staff. The accounting principles are found to be broadly in line with the methodology of the IMF with some departures related to market valuation. The accounting and valuation methodology implemented by the ODCs in Jordan are broadly in line with the recommended compilation practices identified in the Monetary and Financial Statistics Manual and Compilation Guide. Considering the change in the source data since 2014, the mission re-mapped the source data, using data from the aggregated balance sheet of the banking sector and the accompanying schedules through a bridge table. The mission built a time series for all the required data and created a tool linking the data to the Standardized report forms. The tool provides CBJ staff with a simpler method for data compilation.